PENGARUH AROMATERAPI TERHADAP PENURUNAN NYERI PADA PASIEN DENGAN KANKER KOLOREKTAL : A SCOPING REVIEW: The Influence Of Aromatherapy On Pain Reduction In Patients With Colorectal Cancer : A Scoping Review - Nia Rosliany; Wahdini, Rizqa; Ribka Sabarina Panjaitan (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Pain is a prevalent symptom among cancer patients, accompanied by fatigue, sleep disturbances, anxiety, and depression. Aromatherapy, a non-pharmacological method, can safely reduce pain without negative side effects. It involves the use of essential oils as therapeutic agents, absorbed through the skin or olfactory system. This study aims to evaluate the impact of aromatherapy on pain reduction in colorectal cancer patients. This study uses a scoping review methodology based on PRISMA guidelines. The review encompasses three databases: PubMed, Sage, and ScienceDirect, covering the period from 2019 to 2024. Specific search terms were utilized based on inclusion criteria for article selection. Out of 2403 research articles, six were chosen after screening abstracts and full texts to identify studies meeting the inclusion criteria. The analysis identified various types of aroma therapy used for pain reduction. The studies reviewed indicated that aromatherapy was administered through massage and inhalation using essential oils like lavender, lemon, peppermint, geranium, and others. Aromatherapy showed significant positive effects in reducing pain compared to placebo or usual care control groups, as measured by the visual analog scale (VAS). The study's findings suggest that aromatherapy effectively reduces stress, depression, and pain perception in patients with colorectal cancer.   Keywords:  Aroma therapy; Colorectal Cancer; Pain